2009
DOI: 10.1111/j.1754-9485.2009.02063.x
|View full text |Cite
|
Sign up to set email alerts
|

Work stress, satisfaction and burnout in New Zealand radiologists: Comparison of public hospital and private practice in New Zealand

Abstract: Different aspects of work stress, job satisfaction, level of burnout and psychiatric morbidity were evaluated in New Zealand radiologists. The present study aims to identify differences in radiologists' work stress, job satisfaction and professional burnout between public hospital and private practice work environments. A questionnaire consisting of various aspects of radiology-specific work stress and job satisfaction was sent to all radiologists in New Zealand. Burnout was assessed with the Maslach Burnout I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 6 publications
2
24
2
1
Order By: Relevance
“…Besides, it also supports the notion that depersonalization as a kind of response approach to emotional exhaustion is closely related to it in order to protect physicians without suffering over-empathy. Unfortunately, our results do not correspond with other some reports [10,12], which had noted a high level of emotional exhaustion and reduced personal accomplishment with a low level of depersonalization among clinic physicians. This inconsistence might partially stem from the difference of division method besides the sample source or the result of some discrepancies on the medical model and regulation among different countries.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Besides, it also supports the notion that depersonalization as a kind of response approach to emotional exhaustion is closely related to it in order to protect physicians without suffering over-empathy. Unfortunately, our results do not correspond with other some reports [10,12], which had noted a high level of emotional exhaustion and reduced personal accomplishment with a low level of depersonalization among clinic physicians. This inconsistence might partially stem from the difference of division method besides the sample source or the result of some discrepancies on the medical model and regulation among different countries.…”
Section: Discussioncontrasting
confidence: 56%
“…Additionally, a number of descriptive studies in connection with burnout so far had been conducted among clinical physicians such as anesthetists, radiologists, urologists, pediatricians and oncologists in many countries, showing that there were different degrees of burnout symptom for employees in this profession [8][9][10][11][12]. However, the previous studies have mostly focused on certain branches of medical practice, and there is little information about the integrated situation of occupational burnout among the population of physicians covering all specialties [13].…”
Section: Introductionmentioning
confidence: 99%
“…one of the highest reported rates among surgical 8,25,33,37,44,45 and nonsurgical specialties, 10,13,14,26,27,31,32,40 including those in previously published reports for neurosurgeons (Table 9). 7,23,37 Burnout was associated with malpractice litigation and uncertainty regarding future earnings and health care reform, which was also shown to decrease the odds of being satisfied with neurosurgery.…”
Section: Discussion Study Findingsmentioning
confidence: 95%
“…In a research with 136 radiologists in New Zealand, Lim and Pinto (2009) observed that in comparison with physicians practicing in the private service, physicians in the public service presented higher rate of stress and burnout associated to professional dissatisfaction. Conflicts with time demands constituted the main source of stress at work, affecting 59% of radiologists in the public service, besides the complaint by 38% concerning low remuneration and higher proportion of hospital patients with complex and severe diseases.…”
Section: Studymentioning
confidence: 99%